Dissolvable polymeric microneedles loaded with aspirin for antiplatelet aggregation - Baorui Wang; Suohui Zhang; Guozhong Yang; Zequan Zhou; Mengzhen Xing; Han Liu; Aguo Cheng; Yunhua Gao (Elsevier, 2023)
To reduce mucosal damage in the gastrointestinal tract caused by aspirin, we developed a dissolvable polymeric microneedle (MN) patch loaded with aspirin. Biodegradable polymers provide mechanical strength to the MNs. The MN tips punctured the cuticle of the skin and dissolved when in contact with the subcutaneous tissue. The aspirin in the MN patch is delivered continuously through an array of micropores created by the punctures, providing a stable plasma concentration of aspirin. The factors affecting the stability of aspirin during MNs fabrication were comprehensively analyzed, and the hydrolysis rate of aspirin in the MNs was less than 2%. Compared to oral administration, MN administration not only had a smoother plasma concentration curve but also resulted in a lower effective dose of antiplatelet aggregation. Aspirin-loaded MNs were mildly irritating to the skin, causing only slight erythema on the skin and recovery within 24 h. In summary, aspirin-loaded MNs provide a new method to reduce gastrointestinal adverse effects in patients requiring aspirin regularly.